Neuropsychiatric involvement in juvenile-onset systemic lupus erythematosus: Data from the UK Juvenile-onset systemic lupus erythematosus cohort study. (October 2021) - Giani, Teresa; Smith, Eve MD; Al-Abadi, Eslam; Armon, Kate; Bailey, Kathryn; Ciurtin, Coziana; Davidson, Joyce; Gardner-Medwin, Janet; Haslam, Kirsty; Hawley, Dan P; Leahy, Alice; Leone, Valentina; et al.
Introduction: Juvenile-onset systemic lupus erythematosus (JSLE) is a rare autoimmune/inflammatory disease with significant morbidity and mortality. Neuropsychiatric (NP) involvement is a severe complication, encompassing a heterogeneous range of neurological and psychiatric manifestations. Methods: Demographic, clinical, and laboratory features of NP-SLE were assessed in participants of the UK JSLE Cohort Study, and compared to patients in the same cohort without NP manifestations. Results: A total of 428 JSLE patients were included in this study, 25% of which exhibited NP features, half of them at first visit. Most common neurological symptoms among NP-JSLE patients included headaches (78.5%), mood disorders (48.6%), cognitive impairment (42%), anxiety (23.3%), seizures (19.6%), movement disorders (17.7%), and cerebrovascular disease (14.9%). Peripheral nervous system involvement was recorded in 7% of NP-SLE patients. NP-JSLE patients more frequently exhibited thrombocytopenia (<100 × 10 9 /L) ( p = 0.04), higher C-reactive protein levels ( p = 0.01), higher global pBILAG score at first visit ( p < 0.001), and higher SLICC damage index score at first ( p = 0.02) and last ( p < 0.001) visit when compared to JSLE patients without NP involvement. Conclusions: A significant proportion of JSLE patients experience NP involvement (25%). Juvenile-onset NP-SLE most commonly affects the CNS and is associated with increased overall disease activity and damage.